2008
DOI: 10.1016/j.bcp.2008.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal liver Cyp2c and Cyp2d expression and activity during rat pregnancy

Abstract: During human pregnancy, CYP2C9, CYP2C19, and CYP2D6 activities are altered. The aim of the current study was to determine if this phenomenon can be replicated in the rat, and to evaluate the mechanisms that contribute to the changes in Cyp2c and Cyp2d activity during pregnancy. The intrinsic clearance of dextromethorphan O-demethylation, a measure of Cyp2d2 activity, was decreased 80% at both days 9 and 19 of gestation when compared to non-pregnant controls. The decreased intrinsic clearance was a result of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
2
31
2
Order By: Relevance
“…This result is noteworthy because the decreased CYP1A2 activity observed in the rat is in close agreement with the 45 and 65% decrease in caffeine oral clearance during mid-and late pregnancy (Tracy et al, 2005). In contrast to the gestational stage-specific changes in mRNA and protein of CYP2D and CYP2C enzymes during rat pregnancy (Dickmann et al, 2008), no significant differences were observed between gestational stages in CYP1A2 activity or expression. This finding again highlights the fact that the effects of pregnancy are specific for a given P450 enzyme, and the mechanisms that result in altered P450 expression and activity during pregnancy vary between isoforms.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…This result is noteworthy because the decreased CYP1A2 activity observed in the rat is in close agreement with the 45 and 65% decrease in caffeine oral clearance during mid-and late pregnancy (Tracy et al, 2005). In contrast to the gestational stage-specific changes in mRNA and protein of CYP2D and CYP2C enzymes during rat pregnancy (Dickmann et al, 2008), no significant differences were observed between gestational stages in CYP1A2 activity or expression. This finding again highlights the fact that the effects of pregnancy are specific for a given P450 enzyme, and the mechanisms that result in altered P450 expression and activity during pregnancy vary between isoforms.…”
Section: Resultscontrasting
confidence: 66%
“…Protein levels of CYP1A2 were determined by Western blotting using 10 g of liver microsomal protein from each animal as described previously (Dickmann et al, 2008). Membranes were probed with sheep anti-rat CYP1A2 (1:6000 dilution; Research Diagnostics, Flanders, NJ) and mouse anti-␤-actin (1:4000 dilution; Sigma-Aldrich) primary antibodies in Odyssey blocking solution (LI-COR Biosciences, Lincoln, NE) with 0.1% Tween 20, rinsed, and incubated with IRDye 700DX donkey anti-sheep (1:3000) and IRDye 800CW donkey anti-mouse (1:5000) secondary antibodies (Rockland Immunochemicals, Gilbertsville, PA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies investigated changes in rodent cytochrome P450 (Cyp) isoforms during pregnancy in mice Koh et al, 2011) and rats (He et al, 2005;Dickmann et al, 2008). However, data are lacking for some important Cyp isoforms involved in pesticide metabolism, and the regulation of hepatic Ces or Pon1 levels during pregnancy is not known.…”
Section: Introductionmentioning
confidence: 99%